Peer pressure, parental bonding, self-efficacy, sensation seeking and risk-taking attitude among adolescents - Hanapi, Nur Nadia (2019)
Risk-taking attitude among adolescents in Malaysia have become riskier and more dangerous that lead to the continuity of social problems among adolescents. Past studies proved the relationship between peer pressure, parental bonding, self-efficacy and sensation seeking with adolescent’s risk-taking attitude, however, there are limited studies in identifying the strongest predictors of risk-taking attitude among adolescent. The main objective of the study is to examine the relationship between peer pressure, parental bonding (maternal and paternal), self-efficacy, sensation seeking and risk-taking attitude among adolescents in Selangor. A total of 462 students between the age of 13 to 18 years old were recruited in the study. The respondents were selected through a simple sampling technique. 18 government high schools in 9 selected districts in Selangor were randomly chosen. A self-administered questionnaire was used for the data collection. The questionnaires include The Attitude Towards Risk Questionnaire (ATTRQ), General Self-efficacy Scale (GSE), Parental Bonding Inventory (PBI), and Impulsive Sensation Seeking Inventory (ImpSS). The instrument used in the study was proven to be reliable for the Malaysia population. Data analysis including descriptive, bivariate and multivariate statistic was used. The Pearson’s correlation analyses indicated that age, peer pressure, sensation seeking, parental bonding was significantly related to the adolescent’s risk-taking attitude. The result of t-test showed a significant difference in the risk-taking attitude between the male and female students. The multiple regression analyses revealed that sensation seeking was the strongest predictors of adolescent’s risk-taking attitude followed by peer pressure and paternal bonding. The findings of the study emphasized on the important contribution of both environmental (peer pressure and paternal bonding) and cognitive factor (sensation seeking) in predicting risk-taking attitude among adolescent. Intervention and programs to promote healthy cognitive development as well as bringing awareness on the importance of the father’s role in adolescent development should be considered.